Health Economic Impact of a Multicenter Quality-of-Care Initiative for Reducing Unplanned Healthcare Utilization Among Patients With Inflammatory Bowel Disease. (3rd December 2021) - Almario, Christopher V.; Kogan, Lawrence; van Deen, Welmoed K.; Scott, Frank I.; Singh, Siddharth; Hou, Jason K.; Lum, Donald; Aguilar, Humberto; Betteridge, John; Flynn, Ann; Gerich, Mark; Kaufman, Lia; et al.
Abstract : INTRODUCTION: A multicenter adult inflammatory bowel disease learning health system (IBD Qorus) implemented clinical care process changes for reducing unplanned emergency department visits and hospitalizations using a Breakthrough Series Collaborative approach. METHODS: Using Markov decision models, we determined the health economic impact of participating in the Collaborative from the third-party payer perspective. RESULTS: Across all 23 sites, participation in the Collaborative was associated with lower annual costs by an average of 2, 528 ± 233 per patient when compared with the baseline period. DISCUSSION: Implementing clinical care process changes using a Collaborative approach was associated with overall cost savings. Future work should examine which specific interventions are most effective and whether such cost savings are sustainable.